Social Networking Purposes of Pre-Service Teachers - Unal, Ahmet; Akyuz, Halil Ibrahim (Elsevier BV, 2015)
AbstractThe aim of this study is to identify and analyze the social networking purposes of prospective teachers. In order to gather data social networking usage scale was administered to pre-service teachers. The scale was developed by Karal and Kokoç in 2010 and its internal validity Cronbach Alpha coefficient was found to be 0.83 while test-retest reliability was found as 0.91. A total of 187 teacher candidates from various departments participated in the research. Statistical analysis of the gathered data were done through SPSS program. Most of the teacher candidates indicated that they are interested with computer and internet and only a minor group stated that they are not interested with computer at all. A great majority of prospective teachers stated that they are using social networks for educational purposes.
Keywords: Social networking; Prospective teachers’ networking habbits; 4. Education